Estilo de vida, antropometria e aptidão física relacionada à saude em escolares de Blumenau, SC - Reis, Luiz Francisco (2004)
The objective of this study was to verify lifestyle and relate this to anthropometry and Physical Fitness Related to Health (PFRH) among schoolchildren from the city of Blumenau in the state of Santa Catarina, SC, Brazil. The sample was composed of 1083 subjects, 543 boys and 540 girls, between the ages (decimal method) 6.50 and 17.49, enrolled in public and private schools in Blumenau. Physical growth was analyzed by means of body mass, stature, cephalic-trunk height, and legs length; arm, waist, hips and calf perimeters, bone diameters of the styloid process of the radius, bi-epi-condyle of the humerus and bi-epicondyle of the femur. Lifestyle was analyzed through a questionnaire, where responses to it were related to anthropometric variables and body composition, together with physical fitness. The PFRH was analyzed through the use of the Physical Best battery tests. All statistical procedures were made by the SPSS-R6, except for the Analysis of Multiple Correspondence (AMC) and Clusters Analyses (CA), by the STATISTICA 6.0 package. To compare growth variables and PFRH with normal distribution, the Student independent t-test (p ≤ 0.05) was used and, for those that did not have normal distribution, the Mann-Whitney U test (p ≤ 0.05) was used. The Crosstabs procedure was used for tabulating the data from the questionnaire; the statistical procedures AMC and the CA were used in order to verify the relationship between lifestyle and PFRH. Based on the results, it may be concluded that: regarding anthropometric variables, body mass, stature, cephalic-trunk height, legs length, arms and waist perimeters begin to show significantly higher values (p ≤ 0.05) in favor of boys starting at 14 to 15 years of age; regarding the perimeter of the hip and calf, only the latter presented difference in favor of boys aged 15 years; in relation to the radio-ulnar diameter, humerus and femur, higher values were found in boys for the majority of those evaluated. The sum of variables TR + SUB e TR + PAM presented significant differences starting at age 14, with higher values in girls (p ≤ 0.05). The percentage of body fat estimated by the Lohman (1986) equation presented significant differences for all ages, except for 9 years old, with higher values for girls (p ≤ 0.05). The BMI did not seem to be a good indicator of the body adiposity index since its results did not behave in a way that was similar with the results found for the total amount of skinfolds and with the results of the Lohman equation. Regarding the category variables (lifestyle), the AMC and CA did not find any relationship between the variables, leading one to believe that the lifestyle variables did not influence the growth or physical fitness variables. In order to verify the German, Italian and Portuguese ethnic groups, and others (admixture), one can verify that the B socio-economic and social classes were encountered the most often, the majority of schoolchildren live in houses and the area most used for recreational or game purpose was the garden or patio of the house, few practice physical activities outside school, spending an average of two hours watching television. A few play video gaes; they spend an average of one hour a day studying. The girls spend about an hour a day helping around the house. The most desirable extra-curricular course was that of a foreign language. The majority goes to and come back from the school by bus; they make on average three meals a day and the girls are more careful with their eating habits than the boys. The PFRH is higher in boys than in girls for all ages (p ≤ 0.05), except in the flexibility test. Regarding the comparison with the AAHPERD criteria, 52.56% of the boys and 60.12% of the girls attend to the criteria referenced